Tailoring Luminescent Solar Concentrators for High‐Performance Flexible Double‐Junction III‐V Photovoltaics (Adv. Funct. Mater. 6/2023). (2nd February 2023) - Lee, Shin Hyung; Baek, Dongjae; Cho, Whibeom; Lee, Nohyun; Kim, Kwangjin; Kim, Jae‐Hun; Kim, Han‐Jun; Kim, Hyeon Ho; Kim, Hyo Jin; Lee, Seungwoo; Lee, Sung‐Min
Abstract : Luminescent Solar Soncentrators In article number 2210357, Sung‐Min Lee, Seungwoo Lee, Hyo Jin Kim, and co‐workers present strategically designed luminescent solar concentrators (LSCs) that can enhance the photovoltaic output power of flexible double‐junction III‐V solar cells. The optimal LSC configuration augments balanced photocurrents of subcells, thereby reporting up to a 50% increase in their output power without noticeable cost raises.